Pelatihan Penerapan Disiplin Positif Sebagai Upaya Peningkatan Kompetensi Guru Di SMP Negeri 2 Puri Mojokerto - Suesthi Rahayuningsih; Asih Andriyati Mardliyah; Achmad Rijanto (CV. Multi Kreasi Media, 2024)
This training activity was part of the Community Partnership Empowerment activity. This activity was carried out in partnership with SMP Negeri 2 Puri which was located in Mojokerto district, East Java province. The Partner was about 8 kilometers from Universitas Islam Majapahit. The background for implementing this training was due to the lack of knowledge and skills of teachers regarding the implementation of positive discipline in schools. This results in a lack of awareness in improving one's own competence, especially in taking part in workshops and utilizing independent teaching platforms. The aim of this training was for partners to have self-awareness and continue to improve their competence by continuously participating in workshops and utilizing the independent teaching platform, so that teachers have the knowledge and skills to plan and manage the implementation of positive discipline in schools. The method of activity carried out was to provide material about the application of positive discipline to teachers, as well as examples of its application in schools. The results of this training activity were based on the results of the pretest that has been carried out, the average score for teacher knowledge regarding the application of positive discipline was 61.0 and teacher skills were 50.0. And based on the results of the knowledge posttest, the average score was 90.5 and skills was 88.5. From this activity it can be concluded that there has been an increase in teacher knowledge about the application of positive discipline by 51.5% and skills by 80.3%.